GrainBot: An Android-Controlled Rice Grain Collector Robot - Masiado , Sunshine L.; Constantino , Anna D.; Cajurao , Jaelord F.; Valenciano , Jayboy V.; Lagayao , Joe Vincent; Dasmariñas , John Sharwin S.; Laud , Renly Jade S. (International Journal of Advanced Science Computing and Engineering, 2025)
Rice, a fundamental dietary staple for over three billion people around the globe, remains subject to significant postharvest losses, even as advancements in production techniques continue to evolve. Traditional sun drying, although cost-effective and environmentally friendly, presents a range of challenges. It requires considerable labor, exposes farmers to potential health hazards, and often results in uneven drying, which adversely affects grain quality. In response to these pressing issues, this research unveils "GrainBot: An Android Controlled Rice Grain Collector Robot," an innovative solution designed to revolutionize rice collection. This agile, two-wheeled robot employs a sophisticated suction mechanism to efficiently collect sun-dried rice, while being wirelessly controlled via a custom-designed Android application. The functionality, usability, efficiency, compatibility, maintainability, reliability, and portability of this system were rigorously assessed against ISO 25010, with input from a diverse group of users, including farmers, agricultural specialists, and IT professionals. The findings from this comprehensive evaluation revealed a grand mean score of 4.61, indicating an "excellent" rating. This indicates not only a high level of user satisfaction but also underscores the system’s effectiveness in automating and refining the rice grain collection process. Ultimately, the proposed GrainBot represents a promising technological advancement, poised to significantly reduce manual labor, minimize health risks for farmers, and enhance the overall efficiency of postharvest rice handling.